2017
DOI: 10.3389/fmicb.2017.01317
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Microdiversity in Novel Kordia sp. (Bacteroidetes) with Proteorhodopsin from the Tropical Indian Ocean via Single Amplified Genomes

Abstract: Marine Bacteroidetes constitute a very abundant bacterioplankton group in the oceans that plays a key role in recycling particulate organic matter and includes several photoheterotrophic members containing proteorhodopsin. Relatively few marine Bacteroidetes species have been described and, moreover, they correspond to cultured isolates, which in most cases do not represent the actual abundant or ecologically relevant microorganisms in the natural environment. In this study, we explored the microdiversity of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(100 reference statements)
1
6
0
Order By: Relevance
“…Hymenobacter sp. belongs to phylum Bactroidetes was also identified in this study by Royo-Llonch et al (2017) who reported that Hymenobacter spp, inhabit different environmental niches like marine, fresh water, air, soil, and glacier. Pseudomonas sp a Proteobacteria identified currently is common in the aquatic environment according to (Mishra et al, 2017) and most strains are known to be phosphate solubilizing bacteria and also produce antagonism to other pathogens (Paul and Sinha, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Hymenobacter sp. belongs to phylum Bactroidetes was also identified in this study by Royo-Llonch et al (2017) who reported that Hymenobacter spp, inhabit different environmental niches like marine, fresh water, air, soil, and glacier. Pseudomonas sp a Proteobacteria identified currently is common in the aquatic environment according to (Mishra et al, 2017) and most strains are known to be phosphate solubilizing bacteria and also produce antagonism to other pathogens (Paul and Sinha, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Despite enriched taxonomic diversity and wide distribution, physiological, ecological, and genomic studies on the genus Kordia have yet to be performed in-depth beyond those on the algicidal activity of K . algicida strains 10 , 18 20 and a recent report detailing microdiversity among uncultured Kordia species identified by single-amplified genomes from a seawater sample of the Indian Ocean 21 .…”
Section: Introductionmentioning
confidence: 99%
“…TARA_039_SRF, were selected for genome co-assembly and description of gene content. These SAGs were tested for microdiversity through MLSA analyses, resulting in 100% identity at the nucleotide level in each marker [69]. The five markers were the 16S rRNA gene, partial 23S rRNA gene and the Internally Transcribed Spacer, that could be amplified in the 10 SAGs; the partial RNA polymerase subunit B, amplified in 5 SAGs;…”
Section: Resultsmentioning
confidence: 99%
“…We have co-assembled 10 Kordia SAGs previously classified as nearly identical genomes [69] into a high-quality draft genome, which is 94.83% complete and meets the set standards regarding contamination (<5%) [11,37]. Recent studies have shown that co-assembling very closely related SAGs helps overcome the main drawback of their genome amplification step: that it rarely exceeds 60% of estimated genome length [36,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation